The Effect of Quality of Service and Corporate Image on Purchasing Decisions - Abdul Khoir (Almana : Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of service quality and corporate image on purchasing decisions at Alfamart South Tangerang Hospital. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study the quality of service significantly influence purchasing decisions by 40.3%, the hypothesis test obtained t count> t table or (7.967> 1.986). The company's image has a significant effect on purchasing decisions by 37.2%, the hypothesis test is obtained t count> t table or (7.466> 1.986). Service quality and corporate image simultaneously have a significant effect on purchasing decisions with a regression equation Y = 11,931 + 0,380X1 + 0,332X2 and the contribution of influence is 48.7%, the hypothesis test is obtained F count> F table or (44,091> 2,700).